2022
DOI: 10.1108/ijmpb-09-2021-0234
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of key precursors of megaproject crises

Abstract: PurposeDetecting precursory signals is critical to increasing the resilience of megaprojects to crises. This study aims to investigate key crisis precursors to better apprehend traces of megaproject crises and proactively respond to approaching crises, thereby increasing project resilience.Design/methodology/approachDrawing on the theory of weak signals, 25 potential precursors of megaproject crises are extracted. Using exploratory structural equation modeling (ESEM), four models were tested to identify key cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Despite, the abundance of crisis management strategies, there is limited literature available on the crisis management framework. The existing studies on crisis management have devised strategies which can only be implemented to megaprojects (Wang and Pitsis, 2020;Iftikhar et al, 2021;Wang, 2022) and specific industries, such as housing projects (Patil et al, 2016), infrastructure project (Van Os et al, 2015) and software projects (Sangaiah et al, 2018). Moreover, contemporary research gives importance to crisis, but we find that the integrated crisis management process model is not developed for PBOs which can provide guidance to PBOs in crisis situations.…”
Section: Crisismentioning
confidence: 91%
See 1 more Smart Citation
“…Despite, the abundance of crisis management strategies, there is limited literature available on the crisis management framework. The existing studies on crisis management have devised strategies which can only be implemented to megaprojects (Wang and Pitsis, 2020;Iftikhar et al, 2021;Wang, 2022) and specific industries, such as housing projects (Patil et al, 2016), infrastructure project (Van Os et al, 2015) and software projects (Sangaiah et al, 2018). Moreover, contemporary research gives importance to crisis, but we find that the integrated crisis management process model is not developed for PBOs which can provide guidance to PBOs in crisis situations.…”
Section: Crisismentioning
confidence: 91%
“…The existing studies on crisis management have devised strategies which can only be implemented to megaprojects (Wang and Pitsis, 2020; Iftikhar et al. , 2021; Wang, 2022) and specific industries, such as housing projects (Patil et al. , 2016), infrastructure project (Van Os et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, according to the theory of weak signals, the staff’s capability to recognize and address crisis antecedents permits prompt intervention to prevent and minimize impending crises before they occur, thereby boosting project resilience (Wang, 2022). However, it is still unclear how staff members in these situations acquire their vision.…”
Section: Literature Review: Leadership and Visionary Capabilitiesmentioning
confidence: 99%
“…We contend that when organizations make efforts to create a shared vision, staff members learn how to conceptualize a vision, which aids in the development of visionary capacities to make projects resilient. Similarly, based on a questionnaire survey, Wang (2022) investigated key crisis precursors to better apprehend the traces of megaproject crises and proactively respond to approaching crises, thereby increasing project resilience. The author found that one of the key precursors to project resilience is the project participants' knowledge and their being responsible.…”
Section: Visionary Capabilitiesmentioning
confidence: 99%
“…Megaprojects are essential in the development of communities, as they offer employment, economic growth and innovation. Megaprojects are of great importance for national economy and social development (Wang, 2022). Project Management Institute (2017) defined projects as a series of distinctive, multifaceted and associated tasks, which possess a shared goal and are assigned to result in a definite time, a fixed budget, and recognised requirements.…”
Section: Introductionmentioning
confidence: 99%